The Effect of Implementing the Discovery Learning Model on Students Ability to Design Biology Learning Modules Based on Scientific Literacy - Marwah, Andi Sitti (Al-Alam: Islamic Science Education Journal, 2025)
This study aims to examine the effect of the Discovery Learning model on the ability of students in the Biology Education Study Program at the University of Muhammadiyah Maluku to develop modules containing four indicators of scientific literacy: scientific content, learning context, scientific process, and scientific values and attitudes. The method used was quantitative with a quasi-experimental nonequivalent control group design. The sample consisted of two classes, namely the experimental group and the control group. The results showed a significant increase in the experimental group, with an average pretest to posttest score increasing by 18.3 points, while the control group only increased by 8.3 points. The final module score was also higher in the experimental group (86.5) compared to the control group (75.7). These findings confirm that Discovery Learning is effective in improving the ability to design scientific literacy-based modules comprehensively.